Digital Literacy Movement Through Empowering Elderly Groups in Interacting on Digital Platforms in Bengkulu City - Gushevinalti Gushevinalti; Mas Agus Firmansyah; Azahar Kasim (Asosiasi Profesi Multimedia Indonesia, 2023)
In the increasingly advanced information technology era, digital literacy has become an important skill to face the challenges and opportunities offered by digital platforms. However, elderly people often face difficulties in developing these skills. Therefore, this service was carried out to explain and analyze the digital literacy movement involving groups empowering elderly people to interact on digital platforms in Bengkulu City. The service method used is a participatory fun education method, including peer group training, namely providing material through small groups of 10 people with one facilitator and demonstrating directly with props, as well as a mentoring method facilitated by the service team in the form of a WhatsApp group by including all Elderly participants including facilitators for 1 month. The research results show that the digital literacy movement through empowering elderly groups in Bengkulu City has had a positive impact. Through proper training and support, seniors can improve their knowledge and skills using digital platforms. They are able to overcome obstacles such as technological incomprehension, fear and physical limitations that they may face. This service also reveals the importance of an inclusive and sustainable approach in empowering the elderly group in digital literacy. Support from government, community institutions, and families is critical in ensuring older adults have adequate access to necessary training and resources. Apart from that, it was also found that the existence of community and collaboration between elderly people can be an important factor in facilitating the exchange of knowledge and experience in using digital platforms.